An Analysis Of Energy And Nutrient Content In High Energy Natural Isotonic Drink (Isopower) - Nurulfuadi; Dinda Widi Wisudarsari; I Made Tangkas; Ummu Aiman; St. Ika Fitrasyah; Desmeli; Husna, Saadatul (Gema Wiralodra, 2024)
Isotonic drink is the carbonated or non-carbonated drink product used to subtitute the fluid lost in the body. Lack of fluid in the body can cause muscle fatigue until causing the performance decrease in athlete. Isotonic drink can accelerate the return of body fluid compared to water. The purpose of this research was to analyze the content of energy, sodium, potassium, and Vitamin C in isotonic drink with raw material coconut water, pure coconut oil, bee bread, palm vinegar, and honey as high energy natural istotonic drink. The research design used was descriptive observation based laboratory test. The data analysis employed SPSS 22 programs namely by carrying out descriptive test until obtained the average for each isotonic namely 247,491 kkla, sodium 77,085 mg.kg, potassium 1000,785 mg/kg and Vitamin C 2,112 mg. This research concluded that the energy drink content has fulfilled the quality specification of isotonic drink, while the sodium and potassium level do not fulfill the quality specification of isotonic drink yet. Likewise with the Vitamin C content which also does not fulfill the Referrence of Nutrition Label namely 10%.